Implementation of 7 Good Habits: Deep Learning Policy Analysis in Harjasari State Elementary School 01 - Marlina, Mina; Dwi Rahmawati, Hasna; Azzahra, Zayeha; Khusnul Lathifah, Zahra (Jurnal Pendidikan dan Profesi Keguruan, 2026)
​This study analyzed the implementation of the Seven Good Habits program in shaping student character through a deep learning approach at Harjasari State Elementary School 0 in Bogor, Indonesia. Using a descriptive qualitative method, data were collected through semi-structured interviews with three grade 5 teachers, classroom observations, and document reviews. Thematic analysis identified key patterns in teachers’ roles, school policies, and character outcomes. The results indicated that the Seven Good Habits program effectively fostered self-regulation, social interaction, and moral reflection, with 78% of students showing positive behavioral improvement in discipline, empathy, and cooperation after one semester. Deep learning principles, reflection, collaboration, and contextual learning enhance program sustainability. Despite challenges, such as limited facilities and uneven teacher readiness, adaptive strategies and supportive policies have mitigated these barriers. The findings highlight the importance of synergy between deep pedagogical practices, school policy, and parental involvement in achieving meaningful character education in primary schools.​